Lear on Irony and Socratic Method - Futter, Dylan (Conatus - Journal of Philosophy, 2023)
In “The Socratic Method and Psychoanalysis,” Jonathan Lear argues that Socrates’ conversations seek to draw out an irony that exists within human virtue. In this commentary, I suggest that Lear should identify irony with aporia to align his interpretation with Plato’s texts and capture the epistemic dimension of Socrates’ method. The Socratic dialogue is a form of inquiry that encourages the interlocutor to carry on the inquiry. The irony of aporia is that the interlocutor grasps his life’s principle by recognising that he does not know what it is.